Implementation Of Employee Competencies In Improving Organizational Performance Section Of Central Administration Strategy Political Policy, Legal And Domestic Government Ministry Of Home Ministry - Tri Subekti; Veithzal Rivai Zainal; Azis Hakim (Dinasti Publisher, 2025)
The Administration Section of the Center for Political Policy, Legal and Domestic Government Strategy at the Ministry of Home Affairs is required to make a positive contribution through good performance, considering that organizational performance depends on employee performance. Employee performance both individually and in groups is very important for institutions in managing, organizing, managing and using human resources so that they can function productively, effectively and efficiently. This research method is qualitative research with a descriptive case study design. The research instrument was observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation and drawing conclusions and verification. Competency influences the achievement of organizational performance values. Competence is one of the determining factors for employee performance. High competency can encourage employees to work well. To improve performance, the Administrative Section of the Center for Political Policy, Legal and Domestic Government Strategy at the Ministry of Home Affairs can pay attention to employee competency issues, especially those related to employee skills in completing tasks. The Administrative Section of the Center for Political Policy, Legal and Domestic Government Strategy at the Ministry of Home Affairs can also improve education and training to improve employee skills and knowledge. The understanding of the Ministry of Home Affairs' employees of the Center for Political, Legal and Domestic Government Policy Strategy and Standard Operating Procedures (SOP) is good because it can help them carry out their work more efficiently and effectively. Employees understand Standard Operating Procedures. The level of professionalism of the employees of the Central Administration Section for Political, Legal and Domestic Policy Strategy of the Ministry of Home Affairs is good because professional employees will feel safe and comfortable in carrying out their duties, so they are more motivated to work well.